Self Efficacy as a Buffer Against Competitive Anxiety: Self Efficacy and Competitive Anxiety in Sport Competition - Nurudin, Muchlis; Amawidyati, Sukma Adi Galuh (Universitas Negeri Semarang, 2024)
Competitive anxiety and self-efficacy are two important factors in influencing athlete performance. Competitive anxiety is a negative reaction felt by athletes in the face of a match and perceived as a threat. While self efficacy is a person's belief in their ability to perform a specific task. This study aims to determine the relationship between self efficacy and competitive anxiety in volleyball athletes in Gunungpati District This research is a correlational quantitative study. The sample of this study amounted to 60 subjects with the characteristics of volleyball athletes who have participated in matches and live in Gunungpati District. The sampling technique used in this study was a convenience sampling technique. Data collection tools using the SKO scale (Sports Anxiety Scale) totaling 22 items with a reliability coefficient of 0.757, and the ASES scale (Athlete Self Efficacy Scale) totaling 16 items with a reliability coefficient of 0.768. The results of this study indicate that there is a significant negative relationship between self efficacy and competitive anxiety in volleyball athletes in Gunungpati District with a correlation coefficient of -0.476 and significance (p<0.025).